PERTAHANKAN DIVERSIFIKASI ASAL PANGAN POKOK SEBAGAI STRATEGI PENCAPAIAN KETAHANAN DAN PERTAHANAN PANGAN NASIONAL - Roosganda Elizabeth (Universitas Galuh, 2022)
Sovereignty, security and household food defense are defined as the entire population obtaining and being able to consume sufficient food in quantity, quality, nutritious and affordable. The poverty and hunger alleviation policy program is closely related to the fulfillment of the economy and the food needs of the community. Farming and livestock food production aims to meet the needs of the community and as a source of income for the actors involved. Downstream, it is influenced by the availability of safe, nutritious and affordable food along with the community's ability to earn income. The policy is national, affecting sovereignty, food security and defense as well as the sustainability of agricultural development in a wider range, not just production and productivity. With a qualitative descriptive, this paper proposes the empowerment of human resources and agricultural institutions as a strategy for achieving and increasing food sovereignty, security and defense related to aspects of availability and diversification. It is a fact that poverty and hunger are closely related to sovereignty, food security and defense, which is an unfinished agenda. Considering the potential of natural resources, labor, and the environment in rural areas, it is very supportive of the development of agriculture and animal husbandry by integrating an integrated crop-livestock system, both organic and locally specific. Sovereignty, food security and defense can be realized through the function of infrastructure for food supply, distribution and consumption, by business actors in production (producers to post-harvest), distribution and services as well as managing food and nutrition diversification. The importance of adequate food reflects the achievements of the national development policy program, although its sustainability will still be a necessity.